"Good Enough" Governance in the Post-Soviet Eurasia. Issue 4 (4th July 2022) - Baris, Omer F.; Knox, Colin; Pelizzo, Riccardo
ABSTRACT: This paper examines the relationship between governance and economic development. Specifically, it empirically investigates what "good enough" governance means in post-Soviet Eurasia with an emphasis on Central Asia. The subject is crucial for international donors in terms of optimizing interventions to effect change. The findings shed some light not only on which governance dimensions are critical to secure economic growth but also on how much good governance is needed to yield developmental dividends. In this respect, the analyses confirm Grindle's hypothesis that not all governance dimensions affect economic performance. The evidence supports a more radical version of Grindle's argument, namely that political stability is the most crucial component in Central Asia.